2017
DOI: 10.1021/acssuschemeng.6b02515
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sustainable Route for Synthesis of Hydroxyapatite Biomaterial from Biowastes

Abstract: In this study, we demonstrated that hydroxyapatite (HAp) biomaterial can be synthesized entirely from biowastes, i.e., eggshells and urine. Eggshells were cleaned, crushed, and calcined at 900 °C and then the powder was dissolved in water to form an aqueous calcium hydroxide solution. The aqueous solution was mixed with synthetic urine (SU) in stoichiometric amounts corresponding to HAp (Ca/P ratio ∼1.67). Calcium phosphate (CaP) was potentiostatically synthesized on magnesium or stainless steel electrode at c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…In this sense, the production of HA from various wastes is an equally excellent and promising alternative [22]. For example, the use of egg-shell or sea-shell wastes, which represent the most abundant by-products of the food industry, has been found as a very promising sustainable resource to produce HA at a low cost with little impact to the environment [88,119,120,121]. Apart from the method of synthesis, the quality of non-synthetic HA (e.g., purity, grain size, properties) is strongly dependent on the biological source, location, age and fabrication process [1,55,92,93,94,99,100,104,109,111,112,116].…”
Section: Preparation Methods and Synthesis Routes Of Hydroxyapatitmentioning
confidence: 99%
“…In this sense, the production of HA from various wastes is an equally excellent and promising alternative [22]. For example, the use of egg-shell or sea-shell wastes, which represent the most abundant by-products of the food industry, has been found as a very promising sustainable resource to produce HA at a low cost with little impact to the environment [88,119,120,121]. Apart from the method of synthesis, the quality of non-synthetic HA (e.g., purity, grain size, properties) is strongly dependent on the biological source, location, age and fabrication process [1,55,92,93,94,99,100,104,109,111,112,116].…”
Section: Preparation Methods and Synthesis Routes Of Hydroxyapatitmentioning
confidence: 99%
“…The plausible explanation for the carbonate peak found in the nHAp may be from the substitution of the PO 4 3− ions in the nHAp structure. 15,22 Figure 2 displays the XRD models of nHAp packed, eggshell powder and calcinated eggshell powder. Figure 2(a) confirms the presence of calcite in the ovarian powder at characteristic peaks indicated around 35° (2θ).…”
Section: mentioning
confidence: 99%
“…13,14 Globally, it was suggested that approximately 7.7 million tons of eggshell waste were generated in 2014 alone. 15 From an environmental point of view, the majority of waste eggshells produce is not properly handled leading to negative impacts on the environment. 16 Given this concern, using eggshells for the production of nHAp will not only add value to bio-waste which is important for a cleaner and environmentally sustainable products 17 but will also pave way for effective waste management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the hierarchically porous structure of natural biological templates and their composite materials have attracted wide attention due to their unique properties and wide application prospects [20][21][22]. As an agricultural waste, it is estimated that more than 7.0 million tons of eggshell waste in the world were produced every year [23]. ESM is one of the most widely used natural biological templates, and its unique 3D network structure provides its natural advantages with low cost and non-toxicity as a supporting template [24], compared to other biological templates, such as bacterial virus templates [25], algae templates [26], plant templates [27], and DNA templates [28].…”
Section: Introductionmentioning
confidence: 99%